The Taiwanese health care system under efficiency scrutiny - Jonas Schreyögg (Technische Universität Berlin, Fakultät Wirtschaft und Management, 2004)
This thesis describes the status quo of the Taiwanese health care system in the year 2000, 5 years after the reforms, analyses the economic efficiency of single components of the new health care system and searches for possible solutions to solve uncovered problems. For a better understanding of the Taiwanese health care system, the economic, political and demographic environment is described first of all. Although the Taiwanese economy developed rapidly, the health care system was still looking like that of a underdeveloped country. To analyze the efficiency of the Taiwanese health care system it is necessary to have a general look at the possible composition of health care systems and their incentives on the actors of the system. A health care system can be divided in finance and reimbursement. After presenting basic models of financing a health care system, different methods of reimbursing in-patient, out-patient and pharmaceutical services are described. – – Die vorliegende Arbeit untersucht Reformen des taiwanesischen Gesundheitssystems im Hinblick auf ökonomische Effizienz und erarbeitet Verbesserungsvorschläge. Zum tieferen Verständnis des Gesundheitssystems wird zunächst das ökonomische, politische und demographische Umfeld Taiwans dargestellt. Innerhalb der letzten Jahrzehnte hat sich Taiwan von einem Entwicklungsland zu einer starken ökonomischen Macht entwickelt. Politisch ist Taiwan eines der ersten asiatischen Länder, das eine Demokratie etabliert hat. Das Gesundheitssystem Taiwans hielt mit der rasanten ökonomischen Entwicklung des Landes jedoch nicht Schritt und glich bis 1995 eher dem eines Entwicklungslandes.
Keywords: 330